Successful Email Marketing for Businesses Use Email Marketing to Promote a Product, Service, or Brand - Sinicki, Adam (Apress, 2019)
This video will explain how to use email marketing to promote a product, service, or brand. This is considered by many marketers to be the most important way to collect and nurture leads, and yet it is overlooked by a lot of individual creators and bigger businesses. The video will explain the benefits and provide technical and big-picture advice for setting up and becoming successful. You will learn how to set up an autoresponder and add forms to collect details on your site. You will see how to encourage visitors and customers to provide their details, using squeeze pages, free incentives, sign up forms, checkout forms, and advertising. You'll use this to build a highly targeted list which you will keep clean to avoid blacklisting. You'll see how to write emails that get through spam filters and stand out in a crowded inbox. Finally, you'll be able to use this direct communication to build a more engaged audience and generate more sales. What You Will Learn Discover the benefits of email marketing Write for email Use autoresponders Create squeeze pages and work with the appropriate tools Understand leads/lead conversion Use Google Analytics and other tracking methods Who This Video is For Small businesses and blog owners that want to grow and engage their audience. It is also aimed at larger businesses that aren't fully realizing the potential of internet marketing.